Rural enterprise in Mexico: a case of necessity diversification. Issue 4 (12th October 2015) - Bosworth, Gary; McElwee, Gerard; Smith, Rob
Abstract : Purpose: – This paper aims to consider the challenges facing small rural businesses in Mexico in their efforts to be enterprising and sustainable when confronted with severe exogenous pressures. Extant literature on farm diversification has a developed economy focus (Pyysiäinen et al., 2006; McElwee, 2008; McElwee and Smith, 2013), but relatively little has been published in developing economies. Design/methodology/approach: – This paper considers diversification activities of Mexican farmers. It uses case studies, workshops and interviews to determine the barriers facing farmers and farm advisors. Findings: – Farm businesses, particularly those located in drought-prone regions, have benefited from government-sponsored support, but this support needs to now be targeted to develop the entrepreneurial potential of individuals and collectives. Research limitations/implications: – Carried out in one region of Mexico only, and thus, the findings may not be transferable to other regions. Practical implications: – Recruitment of well-qualified, honest farm advisors with entrepreneurial skills is necessary. Farmers need to be given additional training and support to develop both technological and entrepreneurial skills. Social implications: – Encouraging and supporting rural enterprises in Mexico helps to provide opportunities for regions to be economically and socially sustainable. Originality/value: – A first attempt to look at farmers ' diversification strategies using an entrepreneurial framework.